Incidence and factors associated Post-transplantation anemia in kidney transplant patients at a tertiary-care hospital in Thailand - Sayamon Sukkha (2020)
© 2020, Mahidol University - Faculty of Pharmacy. The scarce of standard recommendation for post-transplantation anemia (PTA) has resulted in different anemia approaches among transplant centers. The information of PTA in Thai kidney transplant patients is also lacking. We aimed to study the incidence of PTA during one year after transplantation. Factors associated PTA were investigated in Thai population. We performed a retrospective, cohort study from kidney transplant patients between 2014-2015. The primary objective was the incidence of PTA at one year after transplantation. Pre-defined factors were examined to predict the probability of PTA. Of 259 patients, the PTA incidence at one year after transplantation was 43.6%. Factors that increased risk of anemia included urinary tract infection, UTI (OR 2.170, 95% CI 1.434-3.248, P = 0.001), ganciclovir or valganciclovir (OR 1.522, 95% CI 0.926-2.501, P = 0.097), history of blood transfusion (OR 1.483, 95% CI 1.177-1.868, P = 0.001), history of using recombinant human erythropoietin, rHuEpo (OR 1.381, 95% CI 1.098-1.737, P = 0.006), duration of ESRD (OR 1.032, 95% CI 1.006-1.059, P = 0.015), and recipient's age (OR 1.019, 95% CI 1.009-1.030, P = 0.001). PTA was a common complication (43.6%) after transplantation in Thai kidney transplant patients. UTI, ganciclovir or valganciclovir, history of blood transfusion, history of using rHuEpo, duration of ESRD as well as recipient's age are associated with an increased risk of PTA. This information can assist practitioners to recognize the tendency of anemia and promising factors to proper management in our transplant center.